Pengaruh Pemberian Serat Kelapa Sawit dan Urine Sapi pada Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Putu Aryadika; Any Kusumastuti; Made Same (Politeknik Negeri Lampung, 2015)
Cocoa plants are plantation crops that have high economic value and stable. Cocoa prospects quite good because the market demand is very big commodity. The research was conducted in field trials, Lampung State Polytechnic, fromÂ September 2014 up to February 2015. Experiments conducted with factorial randomized block design with 2 factors and any combination treatment was repeated three times. The first factor, namely the provision of oil palm fiber to the growing media consisting of 0% oil palm fiber and 100% soil, 25% oil palm fiber and 75% land, 50% oil palm fiber and 50% of the land. The second factor, namely the provision of liquid organic fertilizer of cow urine which consists of 0 ml of cow urine, cow urine of 40 ml, 80 ml of cow urine, cow urine and 120 ml. This study was conducted to determine the effect of oil palm fiber and cow urine, as well as the provision of fiber interactions palm and cow urine on the growth of cocoa seedlings. The results showed the provision of oil palm fiber 0% gives better results than the 25% and 50% in high-seed, stem diameter, number of leaves, dry weight and root length stover. Giving cow urine of 40 ml to 120 ml showed better results than without the provision of cow urine on seedling height, stem diameter, number of leaves, dry weight stover, and root length. In general, oil palm fiber giving no effect on the growth of cocoa seedlings and cow urine giving a dose of 40 ml to 120 ml to give effect to the growth of cocoa seedlings. There is interaction granting palm fiber and cow urine on a number of leaves and length of plant roots.Keywords: cocoa seed, cow urine, fiber palm oilPermalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/25